2017
DOI: 10.1016/j.annals.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to achieving cross-border tourism governance: A multi-scalar approach focusing on the German-Czech borderlands

Abstract: This paper aims to identify distinctive obstacles to the establishment of tourism destination governance in both transnational and within-country borderlands. Analysis of the German-Czech borderlands, a region also incorporating within-country borders between three German federal states, indicates the multi-scalar and political contestations of cross-border tourism collaboration. Local tourism projects are generally successful, both on a transnational German-Czech level and between the German states of Bavaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…The governance of destinations, which are strongly shaped by touristic activities, is becoming an increasingly important topic [1][2][3]. Research has investigated the principles of tourism governance under varying settings [4,5]: At an institutional level, research has concentrated on the role of governance for economic performance [6,7], but recently social and environmental aspects of governance have received increased attention [8,9]. Previous studies have reported that tourism governance needs to adopt a holistic understanding of social factors such as citizen participation and collaboration among stakeholders [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The governance of destinations, which are strongly shaped by touristic activities, is becoming an increasingly important topic [1][2][3]. Research has investigated the principles of tourism governance under varying settings [4,5]: At an institutional level, research has concentrated on the role of governance for economic performance [6,7], but recently social and environmental aspects of governance have received increased attention [8,9]. Previous studies have reported that tourism governance needs to adopt a holistic understanding of social factors such as citizen participation and collaboration among stakeholders [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to conduct a discussion between the government of the Republic of Indonesia and the government of PNG to manage the border area. In the case of German-Czech borderland, Stoffelen et al (2017) mentioned the importance of structural cross-border destination management with the multi-scalar approach between the two countries in order to develop tourism destinations in the border area. It is a very good practice to be applied in the management of border tourism in Indonesia.…”
Section: The Impact Of Cross Border Festivalmentioning
confidence: 99%
“…It is also important to conduct a discussion between the government of the Republic of Indonesia and the government of PNG to manage the border area. In the case of German-Czech borderland, Stoffelen et al (2017) mentioned the importance of structural cross-border destination management with the multiscalar approach between the two countries in order to develop tourism destinations in the border area. It is a very good practice to be applied in the management of border tourism in Indonesia.…”
Section: The Impact Of Cross Border Festivalmentioning
confidence: 99%